Sub-national Revenue Mobilization in Latin America and Caribbean Countries: The Case of Venezuela - German Rios; Federico Ortega; J. Sebastian Scrofina (Inter-American Development Bank (IDB), 2012)
This paper analyzes the high fiscal dependence of Venezuelan states and municipalities on the central government and the political economy process embedded in the interaction between the central government and sub-national entities. Also explored is whether there is scope to increase sub-national governments revenues, improve the current intergovernmental transfer system, and reduce horizontal imbalances; of particular importance is analyzing the impact of current transfer mechanisms on sub-national governments revenues volatility. Following a presentation of Venezuelas economic background, public sector and fiscal variables, the paper describes the process of decentralization, inter-governmental transfer mechanisms and revenue volatility, and local governments own revenues. Subsequently presented are sub-national governments fiscal dependence and its determinants, followed by options for revenue mobilization and improving the transfer mechanism. The paper concludes with a summary and policy recommendations.
Keywords: H70; H72; H77; 330